Home Cultures and Idiom Processing: A Short Cut to Encyclopaedic Assumptions of Idioms - Bouherar, Salim (European Scientific Journal, ESJ, 2020)
This paper forms a part of my PhD research on idiom comprehension and processing through home cultures. The article argues that using home cultural assumptions in teaching idioms could result in easy and quick processing of such figurative aspects of speech. Shedding light on the nature of teaching, however, reveals that teaching English in Algeria is a fairly target culture-based process. This can slow the comprehension process and on some occasions, confuse the learner. This paper reveals the results of a set of semistructured interviews and comprehension tests that were conducted with teachers and learners. Learners were divided into two groups and taught throughout a four-week period using teaching materials that assumed home and target culture lessons of idioms, respectively. Students sat for a pre- and a post-test and were also interviewed after finishing the lessons. The results revealed that students recorded positive reactions toward home culture based teaching of idioms. Comprehension tests also reported a significant difference between the two groups’ performance on idiom comprehension.